2021
DOI: 10.3389/fimmu.2021.757231
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Ligases CBL and CBL-B Maintain the Homeostasis and Immune Quiescence of Dendritic Cells

Abstract: Dendritic cells (DCs) are composed of multiple lineages of hematopoietic cells and orchestrate immune responses upon detecting the danger and inflammatory signals associated with pathogen and damaged tissues. Under steady-state, DCs are maintained at limited numbers and the functionally quiescent status. While it is known that a fine balance in the DC homeostasis and activation status is also important to prevent autoimmune diseases and hyperinflammation, mechanisms that control DC development and activation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…Liver fibrosis in dKO mice was autoimmune-unrelated as dKO mice did not manifest autoimmune disorders, which was also confirmed by data using Rag1 −/− dKO mice model [ 36 ]. Although macrophages and NK cells are involved in liver fibrosis, we did not observe an increase in the numbers of liver infiltrating NK cells and macrophages [ 36 ].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Liver fibrosis in dKO mice was autoimmune-unrelated as dKO mice did not manifest autoimmune disorders, which was also confirmed by data using Rag1 −/− dKO mice model [ 36 ]. Although macrophages and NK cells are involved in liver fibrosis, we did not observe an increase in the numbers of liver infiltrating NK cells and macrophages [ 36 ].…”
Section: Discussionsupporting
confidence: 68%
“…Liver fibrosis in dKO mice was autoimmune-unrelated as dKO mice did not manifest autoimmune disorders, which was also confirmed by data using Rag1 −/− dKO mice model [ 36 ]. Although macrophages and NK cells are involved in liver fibrosis, we did not observe an increase in the numbers of liver infiltrating NK cells and macrophages [ 36 ]. Adoptive transfer result indicated that dKO cDC1s could directly initiate or drive liver fibrosis, possibly by creating an inflammatory environment due to their massive hepatic accumulation and elevated basal expression of inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 68%
“… 27 They regulate the development, tolerance, and function of T cells and B cells by modulating signals transmitted by T cell and B cell antigen receptors and co-receptors. 47 Studies have shown that c-Cbl inhibits microglia-mediated neuroinflammation by negatively regulating the PI3K/Akt/NF-κB pathway. 48 Microglia, as active contributors to neuronal damage in PD, play an important role in the inflammatory process caused by PD pathogenesis, and inhibiting microglial activation is considered a promising therapeutic strategy for the treatment of PD.…”
Section: Discussionmentioning
confidence: 99%